A STUDY ON MANAGING DISTRIBUTED AND REMOTE TEAMS IN IT AGILE PROJECTS - Calvina Suhas Maharao (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In recent years, Agile methodologies have become the preferred approach for managing IT projects, especially in organizations that value flexibility, speed, and continuous delivery. With the rise of global teams and the shift towards remote work, managing distributed and remote teams in Agile environments has become a critical area of research. This paper explores the challenges and strategies for managing remote teams in Agile projects, focusing on communication, collaboration, and productivity. It examines existing literature on distributed Agile teams, identifies common barriers faced by project managers, and offers practical solutions for overcoming these challenges. The paper concludes by proposing a framework for managing distributed and remote teams effectively in Agile projects, with insights into technology tools, best practices, and leadership strategies.